2017
DOI: 10.3390/cli5010001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TRMM 3B42 V7 Rainfall Product over the Oum Er Rbia Watershed in Morocco

Abstract: Abstract:In arid and semi-arid areas, rainfall is often characterized by a strong spatial and temporal variability. These environmental factors, combined with the sparsity of the measurement networks in developing countries, constitute real constraints for water resources management. In recent years, several spatial rainfall measurement sources have become available, such as TRMM data (Tropical Rainfall Measurement Mission). In this study, the TRMM 3B42 Version 7 product was evaluated using rain gauges measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 50 publications
(63 reference statements)
5
42
3
Order By: Relevance
“…Jiang et al [19] analyzed the TRMM 3B42 product across a large region of China and obtained higher correlation coefficients in the wet part of the study area, whereas lower r values occurred mostly in relatively dry regions. Although the rainfall over the study area was better estimated in this work than in the studies by Ouatiki et al [41] and Yuan et al [20], the TRMM and Hydroe products showed high error values. Comparing satellite pixels with data from rain gauge stations involves a mismatched spatial scale because the satellite products are extracted from an area of approximately 625 km 2 for the TRMM products and of 25 km 2 for the Hydroe products, unlike the rain gauges that provide punctual rainfall measurements.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Jiang et al [19] analyzed the TRMM 3B42 product across a large region of China and obtained higher correlation coefficients in the wet part of the study area, whereas lower r values occurred mostly in relatively dry regions. Although the rainfall over the study area was better estimated in this work than in the studies by Ouatiki et al [41] and Yuan et al [20], the TRMM and Hydroe products showed high error values. Comparing satellite pixels with data from rain gauge stations involves a mismatched spatial scale because the satellite products are extracted from an area of approximately 625 km 2 for the TRMM products and of 25 km 2 for the Hydroe products, unlike the rain gauges that provide punctual rainfall measurements.…”
Section: Discussioncontrasting
confidence: 68%
“…Hence, the first validation was performed on the smallest possible spatial scale (point-to-pixel analysis) to understand the ability of the satellite products to estimate the daily rainfall at each point represented by the rain gauge stations. Ouatiki et al [41] found low values for the linear relationship (<0.38) at all 19 rain gauge stations across a mountainous watershed in Morocco and explained that the low efficiency of the TRMM 3B42 product was due to the rapid cloud dynamics and the stormy nature of rainfall events in the study region. The authors also observed that the TRMM product had difficulties in estimating rainfall levels over mountainous regions receiving snowfall [41].…”
Section: Discussionmentioning
confidence: 91%
“…Meanwhile, a study carried out in Qinghai Lake Basin, China, shows that TRMM exhibits a poor performance between May and September, which is the dry season [19]. This is consistent with a study carried out in Morocco, which showed that July and August exhibit the lowest correlation coefficients [6]. A study in Circum-Bohai-Sea region, China, showed that the rainfall pattern is more effectively captured by TRMM for the wet region or season than for the dry region or season [20].…”
Section: Introductionsupporting
confidence: 86%
“…A study carried in Northeastern Iberia showed TRMM to exhibit a good performance in regions with minimum precipitation events and a low altitude, and shows a poor performance on the coastal areas and in complex terrains [5]. The impacts of altitude on the TRMM accuracy are consistent with a study carried out by Ouatiki et al (2017) in Morocco that showed that the TRMM product had problems in estimating rainfall rates over mountainous regions [6]. The difficulties are due to the ability of a Precipitation Radar (PR) to obtain the information about the rain event such as the intensity and distribution, the rain type, and other data [7].…”
Section: Introductionsupporting
confidence: 82%
“…The region frequently suffers from water scarcity and droughts and water availability is the main factor influencing socio-economic development, mostly driven by agriculture (Houdret, 2008). The studies of Tramblay et al (2012), Tramblay et al (2016) and Ouatiki et al (2017) are testimony to the relevance of this area. Therefore, developing new strategies to model this watershed is highly relevant to improve water management and assessment of the water availability within the basin.…”
Section: Introductionmentioning
confidence: 98%